Strigolactones Biosynthesis and Their Role in Abiotic Stress Resilience in Plants: A Critical Review - Saeed, Wajeeha (Front Plant Sci, 2017)
Strigolactones (SLs), being a new class of plant hormones, play regulatory roles against abiotic stresses in plants. There are multiple hormonal response pathways, which are adapted by the plants to overcome these stressful environmental constraints to reduce the negative impact on overall crop plant productivity. Genetic modulation of the SLs could also be applied as a potential approach in this regard. However, endogenous plant hormones play central roles in adaptation to changing environmental conditions, by mediating growth, development, nutrient allocation, and source/sink transitions. In addition, the hormonal interactions can fine-tune the plant response and determine plant architecture in response to environmental stimuli such as nutrient deprivation and canopy shade. Considerable advancements and new insights into SLs biosynthesis, signaling and transport has been unleashed since the initial discovery. In this review we present basic overview of SL biosynthesis and perception with a detailed discussion on our present understanding of SLs and their critical role to tolerate environmental constraints. The SLs and abscisic acid interplay during the abiotic stresses is particularly highlighted. Main Conclusion: More than shoot branching Strigolactones have uttermost capacity to harmonize stress resilience.